Kyorstovo 1: a new burial ground of the period of Roman influences in North-Western Russia - Juškova, Marija; Kulešov, Viačeslav (Archaeologia Lituana, 2011)
Archaeological evidence on the culture of the population of North-Western Russia in the period of Roman influences is extremely scarce (Кулешов, 2005; Juškova, 2006). An exception is the new group of sites of the culture of stone burial grounds with fences (Tarandgräberkultur) recently revealed in the South-West of Leningrad Oblast. The main area of this culture lies throughout what is now Estonia and northern Latvia. It is represented mostly by burial grounds while the settlement-sites are rare. The cemeteries contain collective burials both with inhumations and creations. The burials are arranged in one or several rows and are encircled by small rectangular stone fences attached to each other. The skeletal remains are found as a rule among layers of stones and limestone chips together with the grave offerings: bronze ornaments (fibulae, rings, bracelets, neck rings), beads, iron utensils (knives, grass cutters, awls) and occasionally weapons (spear and dart heads, shield-bosses).